2019
DOI: 10.1126/sciadv.aav0704
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon damping depends on the chemical nature of the nanoparticle interface

Abstract: The chemical nature of surface adsorbates affects the localized surface plasmon resonance of metal nanoparticles. However, classical electromagnetic simulations are blind to this effect, whereas experiments are typically plagued by ensemble averaging that also includes size and shape variations. In this work, we are able to isolate the contribution of surface adsorbates to the plasmon resonance by carefully selecting adsorbate isomers, using single-particle spectroscopy to obtain homogeneous linewidths, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
168
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 76 publications
13
168
0
1
Order By: Relevance
“…concomitantly or coherently 1,7,15,16 with decay of the LSPR, a phenomenon termed as chemical interface damping. 13 Plasmonic Heating.…”
mentioning
confidence: 99%
“…concomitantly or coherently 1,7,15,16 with decay of the LSPR, a phenomenon termed as chemical interface damping. 13 Plasmonic Heating.…”
mentioning
confidence: 99%
“…31 In a microscopic picture, the surface adsorbates induce inside the metal electric dipoles that act as additional scattering centers for plasmon dephasing. 32 The studies of homogeneous plasmon line width of Au nanorods reveal that CID scales inversely with the effective path length of electrons, i.e., the average distance of electrons to the nanorod surface. 33 The contribution of CID to the plasmon energy decay becomes more dominant as the size of plasmonic metal nanoparticles decreases.…”
Section: Influence Of Surface Chemistry On Optical Absorption Of Qsmnpsmentioning
confidence: 99%
“…[163] Experimental observations have shown that a material that is chemically bound to a plasmonic nanoparticle can lead to the acceleration of the plasmon dephasing and thus CID. [164] In this case, plasmon decay can occur by directly generating hot electrons in the electron accepting states on the adsorbate, leaving a hot hole on the metal. In comparison, direct electron transfer is considered to be more efficient than indirect electron transfer, as the latter suffers from significant losses due to electron-electron scattering.…”
Section: Hot Charge Carrier Generation and Transfermentioning
confidence: 99%